Knots Post-Lacanian Psychoanalysis, Literature and Film - Rabaté, Jean-Michel (Taylor & Francis, 2019)
This collection of specially commissioned essays offers a wide array of new psychoanalytic approaches impacted by Lacanian theory, queer studies, post-colonial studies, feminism, and deconstruction in the domains of film and literature.